Correlation of Frequent Complete Denture Fabrication Errors with patients’ Demographic Factors, Stages of Complete Denture Fabrication and PDI - Rafid Ahmad Malik, Besam Babar, Talha Ahmad Malik, Junaid Ali, Chaudhry Usman Azhar, Rohma Umar Khan, Khezran Qamar, Sajid Naeem (Pakistan Journal of Medical & Health Sciences, 2024)
Aim: To determine the frequency of errors during stages of complete denture fabrication by undergraduate BDS students and find out their correlation with patient age, gender and Prosthodontic Diagnostic Index (PDI). Study Design: Cross sectional Observational study Place and duration: Prosthodontic Dept. of Lahore Medical & Dental College, Lahore, from February 2nd 2024 till May 2nd 2024. Methodology: A total of 150 complete dentures made by 75 under graduate students of both gender; working in the department were selected. Students clinical work of denture fabrication was assessed at five stages of denture making and each procedure was clinically assessed at its 4 main steps i.e.; primary impression (impression tray selection, impression mixing, tray placements, impression details), Secondary impression (tray preparation, peripheral boarder molding, wash impression, post dam area recording), Jaw relations (occlusal rims adjustments, establish occlusal plane, vertical relations, centric relation), Tooth setup (canine relation, molar relation, plane of occlusion, ridge relation), Trial and final insertion (esthetics, comfort, finishing and polishing, spot grinding). Results: Maximum of four errors were present at the teeth setup stage of complete denture making 72.7%, followed by jaw relation 29.3%.Maximum number of three errors were found at jaw relation stage 69;46.0% followed by set up of teeth stage; 41; 27.3%. Maximum of two errors were frequently found at trial/ insertion stage 56.0%, followed by secondary impression; 64.7% and primary impression stage 38.0%. Denture fabrication errors at primary impression, secondary impression and jaw relation stages were significantly associated with PDI of the patient; p<0.05, whereas insignificant results were seen with teeth setup and trial/insertion stages. Correlation with respect to gender was statistically insignificant with errors found in all 5 stages of denture fabrication. The correlation of age and errors of primary impression, secondary impression and jaw relation was significant; p<0.05 however no correlation with teeth setup and trial/insertion stages was present. Conclusion: It can be concluded that the most frequent errors made by undergraduate BDS students were at the stages of artificial denture teeth set up and recording maxillomandibular jaw relations and increase in age and PDI complicates the denture fabrication. Keywords: Complete dentures, Errors, Gender, Prosthodontic Diagnostic Index, Undergraduates.